Penglibatan Kerja Kakitangan Kumpulan Sokongan dalam Organisasi - Fauzi, Hussin (1999)
This study was conducted to determine the relation and influence of variables such as demographic, psychological climate and organization commitment toward job involvement among supporting staffs of South Kelantan Development Authority (KESEDAR). About 250 questionnaires was distributed to the respondents and 151 questionnaires were received by the researcher. The data received was analyses using the SPSS version 8.0. The descriptive method was used to analyses the demographic variables and the hypothesis test was conducted to the independent variable using the statistical t-test, ANOVA, Pearson correlation and multiple regression. The study found that the degree of job involvement for the supporting staffs is at the moderate level (mean = 3.450). The demographic analyses shows that 92.7% of the respondent are more than 36 years old and 94.7% of the respondent have been working for more than 10 years. The hypothesis test shows that organization commitment and psychological climate has a significant relationship and influence toward job involvement. Dimensions of psychological climate, which are supporting management, role clarity and contribution has a significant relationship toward job involvement. Therefore, it is recommended that the management should allocate proper attention to the supporting staffs especially in areas that involve problem solving and decision making in the organization. The commitment and contribution given by the workers to the organization should also be recognized.